The vanishing advantage of longevity in Nicoya, Costa Rica: A cohort shift - Luis Rosero-Bixby (Demographic Research)
BACKGROUND: The Nicoya region in Costa Rica has been identified as one of a handful of hotspots of extreme longevity. The evidence supporting this status comes mostly from observing the 1990 and 2000 decades and cohorts born before 1930. OBJECTIVE: To determine how the longevity advantage of older men in Nicoya has progressed in the period 1990 to 2020 and in cohorts born from 1900 to 1950. METHODS: Remaining length of life and adult mortality were estimated using new public administrative records from the electoral system and a Gompertz regression model. A new nationwide survival-time database of 550,000 adult Costa Ricans who were alive at any point during 1990–2020 was put together. RESULTS: The longevity advantage of Nicoya is disappearing in a trend driven mostly by cohort effects. While Nicoyan males born in 1905 had 33% lower adult mortality rates than other Costa Ricans, those born in 1945 had 10% higher rates. The original geographic hotspot of low elderly mortality, coined the Nicoya blue zone, has decreased to a small area south of the peninsula around the corridor from Hojancha inland to the beach town of Sámara. However, Nicoyans born before 1930 who are still alive continue to show exceptionally high longevity. CONCLUSIONS: Surviving Nicoyan males born before 1930 are exceptional human beings living longer than expected lives. Not so for more recent cohorts. The window of opportunity to meet and study pre-1930 individuals is closing. CONTRIBUTION: Hotspots of extreme longevity are probably transient, and their status should be reassessed continuously.